2019
DOI: 10.1177/2053168019848930
|View full text |Cite
|
Sign up to set email alerts
|

Racial bias in legal language

Abstract: Although racial bias in the law is widely recognized, it remains unclear how these biases are in entrenched in the language of the law, judicial opinions. In this article, we build on recent research introducing an approach to measuring the presence of implicit racial bias in large-scale corpora. Utilizing an original dataset of more than one million appellate court opinions from US state and federal courts, we estimate word embeddings for the more than 400,000 most common words found in legal opinions. In a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…It is possible that such models could be improved using foundation models and applied to help judges draft decisions by flagging obvious mistakes in their opinion, as has been discussed in the context of adjudicative agencies Ray and Lubbers 2014]. They can also be used to identify racial biases in legal opinions and help judges revise their opinions accordingly [Rice et al 2019].…”
Section: Opportunities In Lawmentioning
confidence: 99%
“…It is possible that such models could be improved using foundation models and applied to help judges draft decisions by flagging obvious mistakes in their opinion, as has been discussed in the context of adjudicative agencies Ray and Lubbers 2014]. They can also be used to identify racial biases in legal opinions and help judges revise their opinions accordingly [Rice et al 2019].…”
Section: Opportunities In Lawmentioning
confidence: 99%
“…Garg et al (2018) train separate embeddings by decade using the Google Books corpus and show that gender associations track demographic and occupational shifts. The closest analysis to ours is Rice et al (2019), who detect a racial slant in a corpus of U.S. state and federal court opinions. We build on this literature to construct author-specific measures of slant that can be linked to real-world behaviors.…”
Section: Introductionmentioning
confidence: 94%
“…They also found that the fairness gap was particular severe for more serious crimes. Another line of work (Rice et al, 2019;Baker Gillis, 2021;Gumusel et al, 2022) explores representational bias with respect to race and gender analyzing word latent representations trained in legal text corpora. While we agree that representational bias can potentially reinforce unfortunate biases, these may not impact the treatment of individuals (or groups).…”
Section: Related Workmentioning
confidence: 99%